Content management 2.0 - Tramullas, Jesús (Anuario ThinkEPI, 2008)
This short paper reviews the new model of content management that users are implementing with Web 2.0 tools. Usability and integration with social networks are noted as success factors.
Keywords: Content management; Web 2.0.